The influence on perceptions of truthfulness of the emotional expressions shown when talking about failure - Shlomo David; Shlomo Hareli; Ursula Hess (Europe's Journal of Psychology, 2015)
The study aimed to assess whether showing emotion in an organizational inquiry into failure affects perceptions of truthfulness as a function of the match between the explanation of what caused the failure and the emotion expressed. Two web-based studies were conducted. Participants with work experience saw videos of an inquiry and rated the protagonist’s truthfulness. In both studies protagonists who expressed an emotion (anger or shame) were rated as less truthful than protagonists who expressed no emotion, regardless of what the failure was attributed to. In order to not confound effects of emotions with occupational stereotype effects only male protagonists were shown. Showing emotions when questioned is normal. Managers have to be aware of a tendency to count this against the employee. This is the only research focusing on the effects of showing emotions on perceptions of truthfulness in an organizational context.